Impact of migratory flows and socio-environmental factors on dengue epidemiology in Oaxaca, Mexico - Matías-Pérez, Diana; Guerra-Martínez, Araceli; Hernández-Bautista, Emilio; Pérez-Santiago, Alma Dolores; Antonio-Cruz, Alma Lilia; García-Montalvo, Iván Antonio (Frontiers in Sociology, 2025)
Oaxaca, state rich in culture and biodiversity, is currently facing a growing challenge due to the combined effects of mass migration and a significant increase in dengue cases. In recent years, the continuous influx of migrants seeking better opportunities has transformed the region’s social and economic landscape, with a severe impact on public health. Dengue, transmitted by Aedes mosquitoes, has become a critical concern for health authorities, particularly given the favorable climatic conditions for vector proliferation in Oaxaca. The arrival of thousands of migrants, many from countries with endemic dengue outbreaks, has facilitated the introduction of new virus serotypes into the region. Their precarious conditions during their transit, including makeshift shelters with few sanitary facilities, create environments conducive to mosquito proliferation. This is aggravated by the accumulation of garbage and lack of access to potable water. The public health response is urgent and multifaceted, with educational campaigns on dengue prevention targeting both residents and migrants. However, these initiatives face the challenge of reaching a diverse population with different levels of information and access to essential services. Collaboration between non-governmental organizations and government is necessary to address the immediate public health needs of these migratory flows.